Models of medieval utopian states in the doctrines of prominent muslim philosophers (Journal of Philosophy Culture and Political Science, 2025)
In our global age, the idea of ​​creating a planetary society or global citizenship is increasingly challenged, while religious, political, economic, and cultural values ​​are progressively becoming globalized. The origins of globalization can be traced back to antiquity – from the rise of powerful empires and the era of geographical discoveries to dynamic economic exchanges, cooperation among world powers, ancient trade routes such as the Great Silk Road, and, most significantly, the emergence of world religions.The development of Arab-Islamic legal thought is rooted in the rise of Islam in the Arabian Peninsula in the 7th century. Within a short period, Arab Semitic tribes transformed into an effective community with an advanced system of governance. Confronted with new political realities, efforts commenced to address administrative challenges not previously encountered since the time of the Prophet Muhammad.The rapid spread and consolidation of Islam, along with its transformation into a global culture, represents one of the most remarkable chapters in world history. The Arab conquest of vast areas of Spain facilitated the introduction of Europe to a syncretic Arab-Muslim culture. Islamic legal doctrine thus emerged as one of the earliest expressions of proto-globalization.Andalusia, a beacon of medieval enlightenment, succeeded in integrating Eastern and Western cultural legacies into a rich and dynamic syncretic tradition. The renowned scientist and thinker Gustave Le Bon, in his fundamental work The History of Arab Civilization, portrayed the Arabs as the revivers of secular science and pioneers of civilizational progress.Keywords: system of governance, planetary society, East, Islam, property, Andalusia.